2018
DOI: 10.1098/rspb.2018.1904
|View full text |Cite
|
Sign up to set email alerts
|

Of molecules, memories and migration: M1 acetylcholine receptors facilitate spatial memory formation and recall during migratory navigation

Abstract: Many animals use complex cognitive processes, including the formation and recall of memories, for successful navigation. However, the developmental and neurological processes underlying these cognitive aspects of navigation are poorly understood. To address the importance of the formation and recollection of memories during navigation, we pharmacologically manipulated turtles (Chrysemys picta) that navigate long distances using precise, complex paths learned during a juvenile critical period. We treated freely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The power of theta rhythm significantly reduces in NMDA ablated or blocked animals, and their function is impaired in terms of spatial navigation and memory (de Oliveira Cabral, 2014; Korotkova, Fuchs, Ponomarenko, von Engelhardt, & Monyer, 2010). Besides NMDA, M1 receptors are extremely expressed and active in the hippocampus so that their inhibition interrupts encoding of memory in the spatial navigation tasks (Dennis et al., 2015; Leaderbrand et al., 2016; Roth & Krochmal, 2018). These receptors can be stimulated by recurring inputs, especially from the medial septum‐diagonal band of Broca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The power of theta rhythm significantly reduces in NMDA ablated or blocked animals, and their function is impaired in terms of spatial navigation and memory (de Oliveira Cabral, 2014; Korotkova, Fuchs, Ponomarenko, von Engelhardt, & Monyer, 2010). Besides NMDA, M1 receptors are extremely expressed and active in the hippocampus so that their inhibition interrupts encoding of memory in the spatial navigation tasks (Dennis et al., 2015; Leaderbrand et al., 2016; Roth & Krochmal, 2018). These receptors can be stimulated by recurring inputs, especially from the medial septum‐diagonal band of Broca.…”
Section: Discussionmentioning
confidence: 99%
“…GABAergic interneurons of the CA1 provide inhibitory feedback to local pyramidal neurons. This modulatory function is vital for the generation and synchronization of theta rhythm (Leaderbrand et al., 2016; Roth & Krochmal, 2018). The downregulation of GABAA receptor's expression alongside other receptors further contributes to the decline in the theta power.…”
Section: Discussionmentioning
confidence: 99%
“…We followed up this work by repeating the experiment with a specific M1 ACh receptor antagonist and found that blocking these receptors not only disrupted the recollection of spatial memories of migrating adults, but prevented naive turtles from forming such memories and learning migratory routes. [99] Pharmacological manipulation of other neurotransmitters and neuromodulators shows similar patterns. For example, given the role of N-methyl-D-aspartate (NMDA) in memory consolidation and long-term potentiation in mammals, [101] Avigan and Powers [39] experimentally manipulated NMDA in painted turtles that had been previously trained on an X-maze.…”
Section: Manipulation Of Biochemical Processes In the Brain Implies Cmentioning
confidence: 98%
“…Scopolamine disrupted the navigation ability of experienced adults, but not juveniles learning to navigate. We followed up this work by repeating the experiment with a specific M1 ACh receptor antagonist and found that blocking these receptors not only disrupted the recollection of spatial memories of migrating adults, but prevented naive turtles from forming such memories and learning migratory routes …”
Section: Integrating Behavior and Mechanism Enhances Our Understandinmentioning
confidence: 99%
See 1 more Smart Citation